Fuzzy Model of Attracting Investments in Zones of Risk Agriculture - Fozilova, Madina; Jurayev, Zarif (International Journal of Engineering and Technology, 2018)
An optimization model for attracting investments in risky farming zones and algorithms for solving problems of risk assessment is given. The two-criterion problem of finding the optimal combination "risk-return" was solved.Â Â